Comportement Phénologique et MorphoPhysiologique de Quelques Génotypes d’orge et de blé - Chafia, Zerafa; Awatef, Ghenai; Mostefa, Benlaribi (European Scientific Journal, ESJ, 2017)
The study which we propose on this agro-diversity requires precise and methodological characterization of some specimens of germplasm. Thus, a number of characteristics relating to the vegetative apparatus, the reproductive system, and the grain were quantified throughout the life cycle of the plant. This is to say that it takes place from the sowing time to the time of maturation of the caryopsis (Grain). The description of three durum wheat genotypes (Triticum durum Desf.), three common wheat genotypes (Triticum aestivum L.), and three of the barley genotypes (Hordeum vulgare L.) was carried out. This was in addition to phenology as well as the production characteristics (Agronomic characteristics) and adaptation characteristics. In particular, water deficit was adopted by the Vegetals Obtentions Protections Union (UPOV) from the year 1981. Also, it was expressed by Soltner in 1982 and 2005. Results obtained through the descriptive sheets and phenology show the existence of interesting intra and inter-specific variability that must be preserved, restored, and valorized. This is, however, performed on the vegetable material that are still available and whose genetic potential must be known precisely. Subsequently, we can suggest that the knowledge of cultivar phenology as well as the establishment of its descriptive sheet, as proposed by UPOV, is valuable as the prerequisite for any breeding program. Moreover, this constitutes a data-bank tow whose reference is made in the preservation and conservation of plant genetic resources.